Pengaruh Fasilitas dan Kualitas Pelayanan Terhadap Kepuasan Konsumen (Studi Kasus di SPBU NO. 14.205.156 Desa Bengkel Kec. Perbaungan Kab. Serdang Bedagai) - Lestari, Ainun; Hutasuhut, Julianto (Jurnal Manajemen Akuntansi (JUMSI), 2021)
The purpose of this study was to determine the influence of facilities and quality Services to the satisfaction of the consumers at the gas station No.14.205.156 Village Workshop Kec. Perbaungan. The population in this research is customer satisfaction at the gas station No.14.205.156 Village Workshop Kec. Perbaungan, a total of 600 people. The sample in this study amounted to 60 people were taken randomly by using random sampling technique. This type of research is quantitative research. Instrumentpenelitian using a questionnaire or a questionnaire and then analyzed using the method of multiple linear regression analysis Y=7,682+0,461 X1+0,337 X2, which means that the facilities and service quality effect on customer satisfaction. Based on the results can be known that the facility (X1) has a value of t count sebesar5,409dan t table by 1.67 if compared with t then the result 5,409>1,67, so it can be concluded that the facility has positive and significant effect on customer satisfaction (Y). Quality of Service (X2) has a t value of 4,988 if compared with t table then the result 4,988>1,67, so it can be concluded that Service quality has positive and significant effect on customer satisfaction (Y). Simultaneously, the facilities and Service Quality have positive and significant influence on consumer satisfaction. Meaning hypothesis in this study is accepted, it is evident from the value of F count > F table (51,225>3,15). The results of the coefficient of determination shows that the facilities and Service Quality influence on customer satisfaction 64.3%, while the rest of 35.7% influenced by other variables not examined in this study.